When “AA” is long but “A” is not short: speakers who distinguish short and long vowels in production do not necessarily encode a short–long contrast in their phonological lexicon - Chládková, Kateřina; Escudero, Paola; Lipski, Silvia C. (Frontiers in Psychology, 2015)
In some languages (such as Dutch), speakers produce duration differences between vowels, but it is unclear whether they also encode short versus long speech sounds into different phonological categories. To examine whether they have abstract representations for ‘short’ versus ‘long’ contrasts, we assessed Dutch listeners’ perceptual sensitivity to duration in two vowel qualities: [a] and [ɑ], as in the words maan ‘moon’ and man ‘man’, which are realized with long and short duration respectively. If Dutch represents this phonetic durational difference as a ‘short’-‘long’ contrast in its phonology, duration changes in [a] and [ɑ] should elicit similar neural responses (specifically, the mismatch negativity, MMN). However, we found that duration changes evoked larger MMN amplitude for [a] than for [ɑ]. This finding indicates that duration is phonemically relevant for the maan-vowel that is represented as ‘long’, while it is not phonemically specified for the man-vowel. We argue that speakers who in speech production distinguish a given vowel pair on the basis of duration may not necessarily encode this durational distinction as a binary ‘short’-‘long’ contrast in their phonological lexicon.